Transforming history into heritage: applying corporate heritage to the marketing of places. Issue 4 (July 2018) - Wilson, Rick
Abstract This study applies the principles of corporate heritage branding to the marketing of places to showcase how some cities, regions, and countries use their heritage to convey their modern-day relevance to key stakeholders. A two-step, mixed-method research approach is used. Results from a content analysis of print advertisements from an economic development context find evidence of four heritage-focused campaigns. Based on the content analysis, a single historically focused case study is developed using an organization responsible for one of the identified campaigns to highlight how a corporate heritage campaign is used in place branding. Additionally, a place branding framework is presented to assist academics and practitioners with the identification and study of corporate heritage branding in place branding communications.